The Influence of Digital Marketing Strategy in the Development of MSMEs on Economic Growth 2018 – 2022 (Case Study of Digital Advertising MSMEs in Jakarta) - Rizkia Putri Amalia Zukari; Rudy Aryanto (Riviera Publishing, 2025)
As key contributors to Indonesia's economy, MSMEs must adapt to digital advancements to maintain their competitiveness and growth. The study explores effective digital marketing strategies, challenges MSMEs face in adopting these strategies, and potential solutions to overcome these obstacles, aiming to support sustainable economic development. This research examines the influence of digital marketing strategies on the development of Micro, Small, and Medium Enterprises (MSMEs) and their contribution to economic growth, focusing on the 2018-2023 period in DKI Jakarta. This research investigates how digital marketing empowers MSMEs to expand their reach, increase customer engagement, and ultimately drive business growth. This research aims to explain the correlation between effective digital marketing strategies and economic development by analyzing the case of MSMEs in Jakarta that utilize digital advertising. The results of the research on the relationship between digital marketing strategies in MSMEs and economic growth in DKJ Jakarta have a significant favorable influence or relationship on both the variable number of MSMEs on GDP per capita and the variable of MSME workforce on GRDP per capita DKJ Jakarta 2018 - 2022.